2018
DOI: 10.1111/aos.13891
|View full text |Cite
|
Sign up to set email alerts
|

Binocular vision alterations after refractive and cataract surgery: a review

Abstract: To review binocular and accommodative disorders documented after corneal or intraocular refractive surgery, in normal healthy prepresbyopic patients. A bibliographic revision was performed; it included works published before 1st July 2017 where accommodation and/or binocularity was assessed following any type of refractive surgical procedure. The search in Pubmed yielded 1273 papers, 95 of which fulfilled the inclusion criteria. Few publications reporting binocular vision and/or accommodative changes after ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 91 publications
0
15
0
4
Order By: Relevance
“…According to Kushner et al [24], patients with less than 4 D of anisometropia, no prisms in their spectacles, and no history of diplopia or strabismus should be considered to have low risk of postoperative binocular function decompensation. In addition, García-Montero M et al [4] found that most decompensation of binocular vision after CRS were in fact preoperative disorders. In this study, the mean preoperative SE of the CRS group was −1.51±1.15 D with no other signi cant preoperative medical histories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kushner et al [24], patients with less than 4 D of anisometropia, no prisms in their spectacles, and no history of diplopia or strabismus should be considered to have low risk of postoperative binocular function decompensation. In addition, García-Montero M et al [4] found that most decompensation of binocular vision after CRS were in fact preoperative disorders. In this study, the mean preoperative SE of the CRS group was −1.51±1.15 D with no other signi cant preoperative medical histories.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the recruitment pool of potential civilian pilots, the CAAC ultimately approved corneal refractive surgery (CRS) for civilian pilots in 2006 [3]. Previous studies have reported the decompensation of binocular vision anomalies after CRS in clinical populations, such as postoperative strabismus and diplopia [4,5]. However, the impact that CRS may have on binocular visual functions among pilots has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Also, these disorders are more likely to occur if there was a preexisting binocular abnormality such as anisometropia or phoria/tropia before surgery [7].…”
Section: Introductionmentioning
confidence: 99%
“…To increase the recruitment pool of potential civilian pilots, the CAAC ultimately approved corneal refractive surgery (CRS) for civilian pilots in 2006 [3]. Previous studies have reported the decompensation of binocular vision anomalies after CRS in clinical populations, such as postoperative strabismus and diplopia [4,5].…”
Section: Introductionmentioning
confidence: 99%